Selected Factors Related with The Health Literacy in Blood Glucose Level Controlling of Patients with Type 2 Diabetes - Wutthitham, Nawaporn; Srinoppakun, Pimnipa; Wareeratpakorn, Thitiwat (Journal of The Royal Thai Army Nurses, 2021)
This analytic cross-sectional research aimed to study the level of the health literacy and the selected factors related with the health literacy in type 2 diabetes patients. The samples were 405 Patients with uncontrolled blood sugar level. The research instrument consisted of the selected factors and health literacy assessment questionnaires. The reliability was KR 20 and Cronbach’s alpha coefficient at 0.642 and 0.952. Data was analyzed by descriptive statistics and chi-square. The study revealed that health literacy level was fair. Selected factors had no relationship with health literacy. For each dimension analysis, gender related with health access sand services and decision skill, age, education and related disease related with health knowledge and media literacy, occupation, income and disease duration related with knowledge, health communication, and decision skill were shown significantly at .05.